ANALISIS PENGUASAAN GAYA BAHASA â€œPERSONIFIKASI DAN DEPERSONIFIKASIâ€PADA MAHASISWA ANGKATAN 2012 PRODI BAHASA MANDARIN UNIVERSITAS TANJUNGPURA - Adhianti, Denita Yuni; Thamrin, Lily; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractIn learning a language, we will learn about its writings, grammars, as well as vocabularies. The same thing applies when learning Mandarin. Besides learning about its writing, grammar, and vocabulary, we need to learn about its tone as well. We may also learn about the language style to enrich our vocabularies.The objects of this study are the students of the Faculty of Teacher Training and Education of Mandarin language year 2012 Tanjungpura University with a total sample of 37 students. The author used a literature study and questionnaire as the research method. The objective of this study is to understand the mastering ability of students of Faculty of Teacher Training and Education of Mandarin language year 2012 Tanjungpura University towards the personification and de-personification language styles as well as find out whether their HSK (HanyuShuipingKaoshi) abilitiesaffect their skill in mastering those language styles. The author analyzed the study finding based on the studentâ€™s HSK ability levels. Students in HSK level 6 master the personification language style the most with the average percentage of correct answer of 80%, while students in HSK level 5 master the de-personification language style the best with the average percentage of correct answer of 86.67%.Â Keywords: Comparison, De-personification, Language style, Personification